Implementasi Kebijakan Standar Pelayanan Minimal Bidang Kesehatan dalam Upaya Peningkatan Kualitas Pelayanan Kesehatan Lansia: Studi Kasus Puskesmas Sindangkasih Kabupaten Ciamis - Dwitasari, Anita Theresia; Rusmanto , Wieky (Neolectura, 2025)
The implementation of the Minimum Service Standards (SPM) policy in the health sector serves as a strategic instrument of the government to ensure citizens’ rights to quality healthcare services. This study aims to analyze the implementation of the SPM policy in improving the quality of elderly health services at Sindangkasih Public Health Center, Ciamis Regency. A qualitative case study approach was employed to provide an in-depth understanding of the process, challenges, and effectiveness of policy implementation at the primary healthcare level. Data were collected through in-depth interviews, field observations, and document analysis from the local Health Office. The findings reveal that the implementation of SPM at Sindangkasih Health Center remains suboptimal due to limited human resources, weak intersectoral coordination, and insufficient promotive and preventive programs for the elderly. Using Charles O. Jones’s policy implementation framework, the study identifies that the organizational, interpretative, and application dimensions have not functioned synergistically. Theoretically, this research contributes to expanding the discourse on public policy implementation in healthcare, while practically offering recommendations for institutional capacity building, improved coordination, and digital transformation of elderly healthcare services at the community level to ensure equitable and sustainable health services.